2019
DOI: 10.1038/s41467-019-10292-z
|View full text |Cite
|
Sign up to set email alerts
|

Poly(bis-arylimidazoliums) possessing high hydroxide ion exchange capacity and high alkaline stability

Abstract: Solid polymer electrolyte electrochemical energy conversion devices that operate under highly alkaline conditions afford faster reaction kinetics and the deployment of inexpensive electrocatalysts compared with their acidic counterparts. The hydroxide anion exchange polymer is a key component of any solid polymer electrolyte device that operates under alkaline conditions. However, durable hydroxide-conducting polymer electrolytes in highly caustic media have proved elusive, because polymers bearing cations are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
296
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 282 publications
(309 citation statements)
references
References 43 publications
13
296
0
Order By: Relevance
“…5,6 The vast number of studies on AEMs based on different aromatic polymer backbones, including polyethers, polysulfones, polyphenylenes, polybenzimidazoles, etc., has shown that aryl ether links are sensitive to hydrolysis under alkaline conditions, especially if this reaction is activated by nearby electron-withdrawing groups such as sulfone links. [9][10][11][12][13][14][15][16][17][18][19][20] Hence, AEMs based on ether-free aromatic backbones, such as polyphenylenes, 9,[21][22][23] poly(arylene alkylene)s [24][25][26][27][28][29][30][31][32] and sterically protected polyimidazoliums, [33][34][35][36] as well as on aliphatic backbones such as poly(diallyldialkyl ammonium) 37 and polynorbornenes, 38,39 have shown excellent alkaline stability.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The vast number of studies on AEMs based on different aromatic polymer backbones, including polyethers, polysulfones, polyphenylenes, polybenzimidazoles, etc., has shown that aryl ether links are sensitive to hydrolysis under alkaline conditions, especially if this reaction is activated by nearby electron-withdrawing groups such as sulfone links. [9][10][11][12][13][14][15][16][17][18][19][20] Hence, AEMs based on ether-free aromatic backbones, such as polyphenylenes, 9,[21][22][23] poly(arylene alkylene)s [24][25][26][27][28][29][30][31][32] and sterically protected polyimidazoliums, [33][34][35][36] as well as on aliphatic backbones such as poly(diallyldialkyl ammonium) 37 and polynorbornenes, 38,39 have shown excellent alkaline stability.…”
Section: Introductionmentioning
confidence: 99%
“…The nonacidic environment of AEMFCs allows the use of nonprecious metal catalysts, which intensely reduces the cost per kilowatt of power of fuel cell devices . In spite of the latest technological progress related to electrocatalysts and to the understanding of carbonation issues, one of the main remaining challenges in the AEMFCs is the availability of good, stable anion conducting membranes that enable the hydroxide anion and water conduction through the polymeric network, both as an anion exchange membrane (AEM) and as anion exchange ionomers (AEIs).…”
Section: Introductionmentioning
confidence: 99%
“…Former typically takes place at heteroatom linkages in the backbone such as arylene ether, sulphide or sulfone groups, resulting in the cleavage of the polymer main chain and thereby lowering the membranes' mechanical properties. [17][18][19] Therefore, in order to mitigate backbone cleavage, there is a shi towards polymer backbones that are devoid of any those heteroatom linkages 20,21 for long-term alkaline stability. We previously developed such a structure; a series of novel peruoroalkyl and uorene based copolymers (QPAF4) having no heteroatom linkages in the main chain which provided robust membranes with high elasticity due to the unique combination of peruoro chain and aromatics.…”
Section: Introductionmentioning
confidence: 99%